2022
DOI: 10.1039/d1cy01798e
|View full text |Cite
|
Sign up to set email alerts
|

Design of an in vitro multienzyme cascade system for the biosynthesis of nicotinamide mononucleotide

Abstract: Design the adenosine phosphate hydrolysis (APH) pathway multienzyme cascade system for the biosynthesis of nicotinamide mononucleotide (NMN) in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Therefore, the biocascade reaction is promising to be further scaled up with the same yield. Recently, an in vitro multienzyme cascade system for NMN synthesis via adenosine phosphate hydrolysis pathway was developed to generate 9 mM NMN, but the final condition requires 60 mM AMP as the starting material with the addition of 20 mM ATP and 60 mM NAM [45] . According to the initial AMP concentration, its yield is only 15 %.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the biocascade reaction is promising to be further scaled up with the same yield. Recently, an in vitro multienzyme cascade system for NMN synthesis via adenosine phosphate hydrolysis pathway was developed to generate 9 mM NMN, but the final condition requires 60 mM AMP as the starting material with the addition of 20 mM ATP and 60 mM NAM [45] . According to the initial AMP concentration, its yield is only 15 %.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an in vitro multienzyme cascade system for NMN synthesis via adenosine phosphate hydrolysis pathway was developed to generate 9 mM NMN, but the final condition requires 60 mM AMP as the starting material with the addition of 20 mM ATP and 60 mM NAM. [45] According to the initial AMP concentration, its yield is only 15 %. In addition, AMP is a more expensive precursor for PRPP synthesis than xylose.…”
Section: Supernatant Of the Recombinant Strain Culture Applied In The...mentioning
confidence: 99%
“…The results showed that the optimal concentration of EcPPase was 0.5 µM (Supporting Information: Figure S6), and under this condition, the final titer of NMN was increased to 1213 mg/L, with a yield of 90.8% (Figure 7d, Supporting Information: Figure S6), which was a more than 12‐fold improvement of NMN titer over the initial setup (Figure 2c). Recently, several in vitro synthetic pathways used for NMN synthesis have been reported (Ngivprom et al, 2022; Qian et al, 2022; Zhou et al, 2022). Among them, an impressively high NMN titer of 93.5 g/L was achieved by enzymatic phosphorylation of nicotinamide riboside to NMN using a new nicotinamide riboside kinase.…”
Section: Resultsmentioning
confidence: 99%
“…However, the current high price of NMN hampers the widespread use and practical implementation of this molecule. While there have been many efforts to improve the production of NMN by engineering biosynthetic pathways in vivo (Marinescu et al, 2018; Shoji et al, 2021) or in vitro (Qian et al, 2022; Zhou et al, 2022), these efforts have typically explored only a small set of enzyme homologs in their optimization strategies. Hence, productive enzyme homologs and combinations for efficient synthesis of NMN are still required.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current high price of NMN hampers the widespread use and practical implementation of this molecule. While there have been many efforts to improve the production of NMN by engineering biosynthetic pathways in vivo (Marinescu et al, 2018;Shoji et al, 2021) or in vitro (Qian et al, 2022;Zhou et al, 2022), these efforts have typically explored only a small set of enzyme homologs in their optimization strategies. Hence, productive enzyme homologs and combinations for efficient synthesis of NMN are still required.…”
Section: Introductionmentioning
confidence: 99%